2016
DOI: 10.1097/icl.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure After 2 Hours of Small-Diameter Scleral Lens Wear

Abstract: Objectives Compression of episcleral veins or deformation of tissue in the Schlemm canal beneath the landing zone of scleral lenses could elevate intraocular pressure (IOP). We examined the effect of 2 hours of small-diameter scleral lens wear on IOP. Methods Twenty-nine participants, 29 ± 6 years old (mean ± SD) who had no history of eye disease or scleral lens wear were included in the study. Each participant was fitted with a 15-mm Jupiter scleral lens on 1 eye (study eye). IOP was measured in both eyes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 14 publications
3
46
1
Order By: Relevance
“…Speculation that scleral lens wear may cause an increase in intraocular pressure is a matter of some concern within the eye care community [22,. In this population, only one patient was reported to experience a significant increase in intraocular pressure in one eye.…”
Section: Discussionmentioning
confidence: 83%
“…Speculation that scleral lens wear may cause an increase in intraocular pressure is a matter of some concern within the eye care community [22,. In this population, only one patient was reported to experience a significant increase in intraocular pressure in one eye.…”
Section: Discussionmentioning
confidence: 83%
“…Any rise in IOP may also depend on aqueous drainage facility, which might be restricted in some individuals. In addition and as suggested by Nau and colleagues, aqueous drainage may be compromised by lenses with bearing areas at the limbus.…”
mentioning
confidence: 78%
“…For example, the well conducted study by Nau and colleagues found no significant difference between the mean IOP recorded before and during scleral lens wear; however, some subjects were found to have increased pressure. Such findings might be a consequence of increased susceptibility to scleral lens‐induced IOP elevation due to having thinner scleral tissue.…”
mentioning
confidence: 99%
“…Tissue compression will vary with each lens design (primarily influenced by the tangent and curvature of the landing zone, the total lens diameter, and potentially the insertion technique). Tissue compression may affect tear exchange, comfort during lens wear, the extent of conjunctival staining following lens removal, and potentially intraocular pressure given the location of the haptic zone to the canal of Schlemm (Figure ) …”
Section: Anterior Segment Anatomy and Morphometrymentioning
confidence: 99%